(untitled) (Journal of Pharma Insights and Research, 2026)
Scorbutus, a clinical condition involving severe L-ascorbic acid deficiency, is one of the oldest documented nutritional pathologies in human history. While historically synonymous with the Age of Discovery and the tribulations of maritime exploration, the disease remains a relevant clinical entity in contemporary medicine. L-ascorbic acid serves as an indispensable cofactor for prolyl and lysyl hydroxylases, which are fundamental to the post-translational modification and structural stability of collagen. The absence of this micronutrient precipitates a systemic failure in connective tissue integrity, resulting in characteristic symptoms such as perifollicular hemorrhage, gingival degradation, dental mobility, and impaired cicatrization. Early interventions, most notably the controlled experiments conducted by James Lind in the eighteenth century, identified citrus fruits as potent antiscorbutics, though the biochemical mechanisms remained elusive until the isolation of vitamin C in the early twentieth century. Current epidemiological trends indicate that modern cases are predominantly associated with psychiatric disorders, restrictive dietary patterns, malabsorption syndromes, and socioeconomic disparities. Diagnosis is primarily achieved through clinical suspicion and detailed dietary anamnesis, often confirmed by the rapid resolution of physiological anomalies following targeted supplementation. Management is effectively attained through the oral administration of ascorbic acid, yet public health surveillance is necessary to mitigate risks in vulnerable populations, including the elderly, chronic smokers, and pediatric patients with neurodivergent-associated food selectivity. Modern food processing techniques and lifestyle variables significantly influence the bioavailability of vitamin C, requiring strict dietary guidelines and sustained clinical vigilance to prevent the morbidity associated with this entirely avoidable metabolic disorder